Growth, yield, and fruit quality responses of three cucumber (Cucumis sativus L.) varieties to different ethephon concentrations - ., Kusumiyati; Nurul Fajr, Sarah; Sutari, Wawan; Sauman Hamdani, Jajang (Emirates Journal of Food and Agriculture, 2022)
The decline in cucumber (Cucumis sativus L.) production in Indonesia was correlated with sex ratio imbalance. Therefore, ethephon could be used to retard vegetative growth and modify the sex ratio of the cucumber plant towards femaleness to increase yield. This regulator also has the ability to increase fruit quality. The objective of this research was to investigate the growth, yield, and fruit quality responses of three cucumber varieties to different ethephon concentrations. A factorial randomized block design was used and consisted of cucumber variety (Vanesa, Mars, and Roberto) and ethephon concentration (no ethephon, 150 ppm, and 300 ppm). Each treatment was replicated three times. The results revealed that 150 ppm of ethephon reduced vegetative growth and increased the number of female flowers, sex ratio, fruit diameter, and marketable fruits. Roberto variety had the highest sex ratio, fruit length, total carotenoid, flavonoid, and phenolic content. The interaction effect showed that Roberto with 150 ppm of ethephon exhibited the best in male flower number and fruit weight per plant. Overall, the ethephon treatment at 150 ppm and Roberto variety were recommended to increase the yield and quality of cucumber.